Retrograde approach: going further in endovascular techniques dedicated to critical limb ischemia - Augusto,Rita (2020)
Introduction: Endovascular techniques have been revolutionizing the revascularization of patients with chronic limb threatening ischemia (CLTI), showing consistently high limb salvage rates. However, endovascular recanalization of infrapopliteal occlusive disease can be technically demanding and the failure rate for these types of lesions is about 20%. In that case, an alternative vascular access may be required. We report our experience concerning CLTI patients who underwent retrograde access and recanalization of chronic occlusions after failure of anterograde attempts. Methods: Retrospective institutional review of consecutive patients requiring retrograde punctures to obtain endovascular revascularization (2013-2018) - 51 limbs in 50 patients. The primary outcome was to evaluate the technical success and the limb salvage - major-amputation free survival. The secondary outcomes were the rate of major and minor amputation, the global survival of this population and the characterization of the population and the endovascular procedures performed. Results and conclusion: The technical success was achieved in 76,5% of the procedures. The major amputation free-survival rate was 81,4% at 6 months. The femoro-popliteal and distal territories were concomitantly treated in 63,3% of the procedures and isolated distal territory was treated in 32,7%. Femoral approach was always initially performed (90,2% anterograde). Direct revascularization according to the angiosome concept was obtained in 64,6% of the cases. Anterior tibial artery was punctured in 33,3% of cases followed by pedal artery (27,5%), peroneal artery (19,6%), common plantar artery (7,8%), posterial tibial artery above the ankle (3,9%), supra-articular popliteal artery (3,9%), lateral plantar artery (2%) and metatarsal artery (2%). Percutaneous transluminal angioplasty (PTA) was performed in 69,4% of the procedures (2% with Drug Elluting Balloons) and PTA and stenting in 28,6%. During follow-up 19,4% of patients were submitted to major amputation and 29,4% to minor amputation. The rate of healing at 6 months was 43,3%. The results of the retrograde access and recanalization of chronic occlusions are comparable to data reported in the literature, confirming it as a valuable alternative. As so, the retrograde access approach for revascularization of CLTI patients appears to be a safe and effective alternative that expands revascularization options after the failure of a conventional endovascular anterograde approach, allowing the salvaging a greater number of limbs, particularly in patients with significant co-morbidities.